Aplikasi Model GARCH pada Data Inflasi Bahan Makanan Indonesia - Santoso, Teguh (Jurnal Ilmu Ekonomi ASET, 2011)
In the econometric analysis of time series, data with high volatility will bevery risky to be used as a basis for doing forecasting. Included in this analysis is thevolatility of food inflation in Indonesia. Time series data have a tendency to bully theerror variance (error term) are constant over time. Appropriate econometric model toestimate such behavior is called the Autoregressive Conditional Heteroscedasticity (ARCH)model (Engle, 1982) and the Generalized Autoregressive Conditional Heteroscedasticity(GARCH) model developed by Borreslev 1986. This paper attempts to use models ofARCH / GARCH to explain the behavior of food inflation in Indonesia period 2005.1-2010.6, explained by incorporating elements of ARCH / GARCH this will produce abetter estimation.Keywords: time series data, volatility of food inflation, arch and garch.